2009
DOI: 10.1002/cncr.24504
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib or high‐dose imatinib for chronic‐phase chronic myeloid leukemia resistant to imatinib at a dose of 400 to 600 milligrams daily

Abstract: BACKGROUND In patients with chronic-phase chronic myeloid leukemia (CP-CML), imatinib resistance is of increasing importance. Imatinib dose escalation was the main treatment option before dasatinib, which has 325-fold more potent inhibition than imatinib against unmutated Bcr-Abl in vitro. Data with a minimum of 2 years of follow-up were available for the current study of dasatinib and high-dose imatinib in CP-CML resistant to imatinib at daily doses from 400 mg to 600 mg. METHODS A phase 2, open-label study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
136
0
12

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(151 citation statements)
references
References 28 publications
3
136
0
12
Order By: Relevance
“…As previously described, the START-R trial evaluated dasatinib 70 mg twice daily compared with imatinib dosed at 400 mg twice daily in resistant CP-CML patients, and demonstrated that dasatinib gave superior rates of CHR, MCyR, CCyR, MMR and PFS beyond 12 weeks. 36 The START-C trial also evaluated dasatinib in 288 imatinib-resistant patients, and demonstrated that 85% of patients had achieved a new CHR, 51% obtained a new MCyR and 40% had achieved a new CCyR, corroborating the results from the START-R trial. 105 Nilotinib has also been evaluated in several trials for patients with imatinib-resistant CP-CML.…”
Section: Second-generation Kinase Inhibitorssupporting
confidence: 53%
See 2 more Smart Citations
“…As previously described, the START-R trial evaluated dasatinib 70 mg twice daily compared with imatinib dosed at 400 mg twice daily in resistant CP-CML patients, and demonstrated that dasatinib gave superior rates of CHR, MCyR, CCyR, MMR and PFS beyond 12 weeks. 36 The START-C trial also evaluated dasatinib in 288 imatinib-resistant patients, and demonstrated that 85% of patients had achieved a new CHR, 51% obtained a new MCyR and 40% had achieved a new CCyR, corroborating the results from the START-R trial. 105 Nilotinib has also been evaluated in several trials for patients with imatinib-resistant CP-CML.…”
Section: Second-generation Kinase Inhibitorssupporting
confidence: 53%
“…35 When subset data from the international, open-label, randomized Phase II study SRC/ABL Tyrosine kinase inhibition Activity Research Trials of dasatinibFResistant (START-R) trial was analyzed according to the presence of one of the protocol-specified mutations (L248V, G250E, Q252H/R, Y253H/F, E255K/V, T315I/D, F317L and H369P/R), there were more responses to dasatinib than high-dose imatinib, although only two patients with these mutations were treated with imatinib. 36 In patients with imatinib-resistant or -intolerant accelerated phase disease were treated with dasatinib, similar rates of hematological and cytogenetic responses were also seen in those with or without a mutation. 37 For imatinib-resistant or -intolerant patients with either lymphoid or myeloid blast phase-CML (BP-CML), hematological and cytogenetic response rates to dasatinib were independent of the presence or absence of a baseline Bcr-Abl mutation.…”
Section: Spotlightmentioning
confidence: 92%
See 1 more Smart Citation
“…Second, dose escalation of imatinib can improve response rates in patients with inadequate response to standard-dose imatinib, but switching to second-line nilotinib or dasatinib can be more effective [55]. Several studies that evaluated second-line nilotinib [56,57] or dasatinib [56,58] and high-dose imatinib (400 mg BID) have demonstrated significantly higher rates of CHR, CCyR, and MMR with the newer TKIs than with high-dose imatinib. Moreover, PFS in these studies was better with the newer TKIs than with high-dose imatinib.…”
Section: Second and Third Generation Tkismentioning
confidence: 99%
“…According to the results of START-C trial, after 2 months of treatment with dasatinib, CCyR and MMR had been achieved in, respectively, 45% and 37% of IM-resistant, and 78% and 78% of IM-intolerant patients with CML-CP [42]. These effects were much inferior to those obtained for treatment-naïve CML-CP, and, as was to be expected, the effects of dasatinib were rather limited for advanced phase CML [52][53][54]. Similarly, the effect of nilotinib as second-line treatment is also much inferior to that observed in treatment-naïve patients.…”
Section: Sgis As First-line and Second-line Treatmentmentioning
confidence: 90%